2007
DOI: 10.1007/s00792-007-0068-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of microbial eukaryotes in sediment at a deep-sea methane cold seep: surveys of ribosomal DNA libraries from raw sediment samples and two enrichment cultures

Abstract: Recent culture-independent surveys of eukaryotic small-subunit ribosomal DNA (SSU rDNA) from many environments have unveiled unexpectedly high diversity of microbial eukaryotes (microeukaryotes) at various taxonomic levels. However, such surveys were most probably biased by various technical difficulties, resulting in underestimation of microeukaryotic diversity. In the present study on oxygen-depleted sediment from a deep-sea methane cold seep of Sagami Bay, Japan, we surveyed the diversity of eukaryotic rDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 54 publications
8
114
1
Order By: Relevance
“…150-200 protistan clones (Fig. 1 A general overview of all sequences ( largely agrees with observed diversity and total diversity estimates of other molecular protistan diversity surveys in (anoxic) deep-sea environments (Edgcomb et al 2002;Stoeck and Epstein 2003;Stoeck et al 2006;Takishita et al 2007). This further supports the notion that our interface and brine libraries are not primarily reflections of detritus from the water column but at least to a large extent reflects indigenous protistan assemblages.…”
Section: How Abundant and Diverse Is Protistan Life In Bannock Ansupporting
confidence: 81%
“…150-200 protistan clones (Fig. 1 A general overview of all sequences ( largely agrees with observed diversity and total diversity estimates of other molecular protistan diversity surveys in (anoxic) deep-sea environments (Edgcomb et al 2002;Stoeck and Epstein 2003;Stoeck et al 2006;Takishita et al 2007). This further supports the notion that our interface and brine libraries are not primarily reflections of detritus from the water column but at least to a large extent reflects indigenous protistan assemblages.…”
Section: How Abundant and Diverse Is Protistan Life In Bannock Ansupporting
confidence: 81%
“…For example, MAST-9 was only abundant in anoxic samples (Supplementary Figure S5). Previous studies found MAST-9 associated to hydrothermal vents (Massana et al, 2004) as well as anoxic sea sediments (Takishita et al, 2005, Takishita et al, 2007. MAST-12 was also recovered from the anoxic layers of the Black Sea (Supplementary Figure S5), but it was also recovered from the oxic water column in the same as well as in other locations (for example, Oslo, Roscoff and others; Supplementary Figure S5).…”
Section: Adaptation Of Mast Groups To Anoxic Waters and Sedimentssupporting
confidence: 51%
“…Most MASTs branch near Bicosoecida, Blastocystis and Labyrinthulida (Figure 1), the earliest diverging stramenopile lineages (Riisberg et al, 2009;Tsui et al, 2009). After the initial description of MASTs, they have been regularly detected in diverse marine environmental surveys in different marine geographical areas around the world (for example, Richards and Bass, 2005;Takishita et al, 2005;Takishita et al, 2007;Not et al, 2008Not et al, , 2009Orsi et al, 2011). MAST groups are mostly composed of free-living bacterivorous flagellates, with some groups displaying algivorous preferences (MAST-6; Piwosz and Pernthaler, 2010) and other lineages being parasites (Gomez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental molecular surveys have revolutionized our understanding of microbial systems (6). Phylogenetic surveys also have been applied successfully to study the community composition of eukaryotic microbes at several deep-sea sites (7)(8)(9)(10)(11)(12)(13)(14)(15)(16); however, to date, no study has addressed the phylogenetic diversity of eukaryotic microbial life of one of the largest habitats, covering over half of the Earth's surface: the abyssal plains.…”
mentioning
confidence: 99%